Estimation of actual evapotranspiration from remote sensing: application in a semiarid region - García Galiano S.G.; García Cárdenas R. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
The potential of remote sensing for the recommendation and monitoring of irrigation practices is irrefutable. GIS have enabled the development of operational spatio-temporal tools for monitoring agricultural activity which can overcome the uncertainty brought about by problems related to water scarcity and increasing drought events. This paper presents an operational methodology for estimating actual evapotranspiration from Landsat images, and its application in the Region of Murcia (Spain).